MONITORING PH TANAH KELEMBABAN TANAH DAN PENYIRAMAN OTOMATIS PADA TOKO CITRA TAMAN LANDSCAPE MENGGUNAKAN INTERNET OF THINGS DENGAN METODE TIME SERIES - Fatah Ridho Perdana; Niki Ratama (Journal of Research and Publication Innovation, 2024)
Indonesia's abundant plant diversity and tropical climate make soil conditions, especially pH and moisture, very important for optimal plant growth. Soils that are too acidic or alkaline can inhibit plant growth. Internet of Things (IoT) technology offers an innovative solution by enabling real-time monitoring of soil conditions using internet-connected sensors. This research develops a prototype for soil monitoring and automatic watering at Citra Taman Landscape Shop, using pH and soil moisture sensors to activate the automatic watering system. The prototype is designed for continuous development and integration with new technologies. The implementation and testing of the system that uses the Internet of Things (IoT) to monitor soil pH and moisture, as well as automatic watering, has met the planned specifications. The system allows real-time monitoring of important parameters such as soil pH and moisture, and the automatic watering system can be activated based on data sent from the app which is then managed by a microcontroller connected to the IoT network. In addition, time series methods are used to analyze historical data of soil pH and soil moisture, thus enabling prediction of future soil conditions and faster decision-making in soil management. This success demonstrates the effectiveness of IoT technology and the time series method in managing soil conditions for plant maintenance. The results of this study show that the application of IoT at Citra Taman Landscape Store can speed up soil condition handling actions and allow store owners to connect and manage plants more efficiently.